Media reporting of ethnic identity-based violence and personal security challenges in North Shoa, Ethiopia - Genet Zeyede; Agaredech Jemaneh; Yonas Adaye (Cogent Social Sciences, 2024)
The proliferation of ethnic affiliated media following the political reform of 2018 has intensified ethnic identity-based violence in Ethiopia. Nevertheless, the impact of this media platform on personal security has been inadequately investigated. Thus, this study aimed to explore the existing ethnic identity-based violence (EIBV) in relation to ethnic- affiliated media reporting (EAMR) and its consequence on personal security in North Shoa, Efratana Gidim Woreda. A qualitative research approach was utilized. As a result, data were collected through in-depth interviews, focus group discussions, and content analysis of two ethnically affiliated media reports. Thematic data analysis was used. The findings revealed that the historical claims, political narrations and manipulation of ethnic-affiliated media (EAM) to the interests of actors were costing the lives of civilians. Furthermore, EAMR concerning EIBV demonstrated a lack of precision and impartiality. This misrepresentation obscures the actual extent of the violence, inaccurately portraying the perpetrators as victims and the victims as perpetrators. This in turn, reinforces the expansion and escalation of the existing EIBV, which intricate personal insecurity in the area. The finding revealed personal insecurities such as physical injury, death, and moral insecurity among the victims. Based on this, the result suggests that the establishment of EAM needs great caution and strict management of their functioning only in the direction of their purposes. Moreover, the healthy functioning of such kind of media requires strong legal grounds and proper enforcement.